(untitled) (Revista do Centro de Estudos Portugueses, 2006)
Em suas memórias de infância, os escritores quase sempre inserem uma ou mais cenas contendo sinais, freqüentemente em forma de um livro específico, que pressagiariam sua futura carreira literária, muitas vezes em contraste com um cenário de grande pobreza material e intelectual, ou de discriminação e desvalorização da criança. Esse recurso chega a constituir quase um topos na escrita memorialística e foi estudado por Sylvia Molloy, no memorialismo latino-americano, sob a denominação de “a cena da leitura”. Textos tão distantes quanto os de Tolstói e Oswald de Andrade podem ser explorados desse ponto de vista, suscitando questões sobre filiação intelectual. In their memoirs of childhood, writers often insert one or more scenes that bring out pressages, generally under the sign of a specific book, of their future literary career, frequently against a background of great material and intelectual want, in which the child is overlooked and discriminated. This resource can be said to constitute a topos in the genre and has been investigated by Sylvia Molloy concerning Latin American autobiographic writing, under the concept of “the scene of reading”. Authors as far apart as Oswald de Andrade and Tolstoi can be examined from this perspective, giving rise to reflections on intelectual affiliation.